AB1126 Changes in Das28 by Age and Ethnicity Among Patients Attending one Rheumatology Clinic in London, UK. (9th June 2015) - Galloway, J.; Ibrahim, F.; Mian, A.; Gullick, N.; Steer, S.; Lempp, H.
Abstract : Background: There have been few published studies in the UK that examined specifically the impact of ethnicity and age on Rheumatoid Arthritis (RA) outcomes, cross-sectional or longitudinal. From the available literature it seems uncertain whether differences in the clinical phenotype may result from the discrepancy in aetio-pathogenesis, or whether it is a consequence of environmental, cultural and socioeconomic factors. Objectives: To study changes in Disease Activity Score (DAS28) and its components to identify severity of disease by ethnicity among patients with RA attending an outpatient clinic in a diverse inner city population. Methods: All RA patients attending a large teaching hospital outpatient clinic between 2010 and 2014 were identified via a Rheumatology clinic database. The socio-demographic and clinical (DAS28 & HAQ) variables were obtained, including estimates of socioeconomic status using postcodes to obtain indices of multiple deprivation. Ethnicity data were self-reported. A mixed-effects linear model was used to examine the mean difference between ethnicity groups (White Caucasians versus Black patients) in clinical variables throughout follow up, including individual DAS28 components. Comparisons were adjusted for age, gender, disease duration and index of multiple deprivation. Results: 815 RA patients were suitable for analysis: mean age was 62 years; 78% were female; a quarter of patients self-identified as Black (e.g. Afro-Caribbean, African). DAS28 was significantly higher in Black compared to White patients, even after adjustment. Analysis of the individual components revealed that this difference was driven by significantly higher ESR and patient global scores in Black patients. Tender and swollen joint counts were numerically higher, but the differences did not reach statistical significance in adjusted analyses. Disability levels were significantly higher in Black patients. Paradoxically the CRP was significantly lower in Black patients. Conclusions: The disease pattern for Black patients with RA appear to be different in comparison to White Caucasians. Both subjective and objective measures were higher in Black patients. The observed differences may reflect different RA disease phenotypes or different treatment exposures. Significant disagreement was present between ESR and CRP in black patients. Ethnicity is a patient specific factor that clinicians need to take account of both when considering disease assessment and treatment pathways Disclosure of Interest: J. Galloway: None declared, F. Ibrahim Employee of: King's Collge London, A. Mian: None declared, N. Gullick: None declared, S. Steer: None declared, H. Lempp Grant/research support from: NIHR, Health Foundation, ARUK, EU, South London Membership Council, Employee of: King's College London